Teknik Pengukuran Laju Respirasi Produk Hortikultura pada Kondisi Amosfir Terkendali Bagian 2: open system method - Rokhani Hasbullah (PERTETA, 2008)
Abstract The design of modified atmosphere packaging (MAP) requires steady state respiration rate data. The respiration rate of fresh produce is usually measured by the open system method where a steady stream of gas is passed through a respiration jar. It needs gas mixing unit to get certain level of controlled atmosphere (CA) condition and an instrument to analyze gas composition. In this research, a gas chromatograph of Hewlett Packard of HP 5890 series with a thermal conductivity detector and suitable column was used to analyze the composition of oxygen, carbon dioxide and nitrogen simultanously. The measuring result of respiration rate of broccoli under CA conditions indicated that the gas composition gave significant influences. The respiration rate at a constant CO2 concentration decreases with decreasing O2 concentration. Keywords: broccoli, respiration rate, modified atmosphere packaging, gas chromatograph Diterima: 10 Desember 2007; Disetujui: 21 Maret 2008